The State of Bone Mineral Density, Cytokine Status and Endothelial Dysfunction in the Patients with Reflex Manifestations of Lumbar Osteochondrosis and Possible Ways of Their Correction - Babinets, Liliya Stepanivna; Nadkevych, Andriy Longinovych (Journal of Education, Health and Sport, 2015)
Babinets L. S., Nadkevych A. L. The State of Bone Mineral Density, Cytokine Status and Endothelial Dysfunction in the Patients with Reflex Manifestations of Lumbar Osteochondrosis and Possible Ways of Their Correction. Journal of Education, Health and Sport. 2015;5(6):29-36. ISSN 2391-8306. DOI 10.5281/zenodo.18207 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A29-36 https://pbn.nauka.gov.pl/works/562809 http://dx.doi.org/10.5281/zenodo.18207 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.05.2015. Revised 28.05.2015. Accepted: 31.05.2015. The State of Bone Mineral Density, Cytokine Status and Endothelial Dysfunction in the Patients with Reflex Manifestations of Lumbar Osteochondrosis and Possible Ways of Their Correction L. S. Babinets, A. L. Nadkevych Department of Primary Medicosanitary Aid and Family Medicine of the I.Ya. Horbachevsky Ternopil State Medical University, Ternopil Abstract More significant positive evolution of pain syndrome elimination in osteopenia-associated lumbar osteochondrosis in the case the course of meloxicam pharmacopuncture is included in the complex treatment in comparison with the group of conventional treatment (from 100% to 6.7 and 26.35%, respectively). Implication of meloxicam pharmacopuncture in the complex treatment of patients with osteopenia- associated lumbar osteochondrosis resulted in certain decrease of anti-inflammatory cytokines (necrosis factor for tumors-α and interleukin-1) as well as increase of anti-inflammatory interleukin-10 cytokine in comparison with conventional intramuscular drug injection. 3 months’ conventional treatment enhanced by meloxicam pharmacopuncture revealed reliable tendency to the recovery of lost bone weight (2.46±0.04) % according to Young Adult % value) and more substantial decrease (considering NO2 metabolite level). of endothelial dysfunction (from 5.1±0.02 to 3.8±0.05 mcmol/l, p<0.05), what confirmed high anti-inflammatory meloxicam efficacy as well as the practicability of its injection into acupuncture points according to the suggested technique. Key words: reflex manifestations of lumbar osteochondrosis, osteodeficiency, pharmacopuncture, meloxicam (movalis), cytokine status, endothelial dysfunction.